Pengaruh Harga Diskon dan Promosi terhadap Meningkatnya Jumlah Daya Tarik Pelanggan - Rihma Hani; Della Puspita Sari (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The emergence of more advanced technology has the potential to have both positive and harmful effects on people's lives, one of which is the world of business. Since many businesses are currently vying for market share and expanding their consumer base, competition between store owners is now unavoidable. Therefore, in order for a firm to succeed and beat the competition while accomplishing the company's own objectives, it must develop an effective marketing plan. The cost of products and services influences market demand. This prompts business owners to implement promotions and price reductions to draw in more customers. This study takes a literary approach while using qualitative research techniques. This study's objective is to investigate more thoroughly connected to purchasing and selling promotions and discount techniques from the standpoint of Islamic Law.